Effects of xylanase and phytase supplementation in diets containing Moringa oleifera leaf meal on intestinal morphology and the relative size and weight of internal organs of laying hens - Macambira, Gabriel Miranda; Rabello, Carlos Bôa-Viagem; Oliveira, Hélia Sharlane de Holanda; Santos, Marcos José Batista dos; Ribeiro, Apolônio Gomes; Lins Júnior, Oziel Saturnino; Sousa, Lucas Delano Nascimento de; Máximo, Igor Luiz Carvalho; Carvalho, Lucas Rannier Ribeiro Antonino; Fleitas, Odrey Mesa (Frontiers in Veterinary Science, 2025)
Moringa oleifera leaf meal (MOL) can be an alternative food in poultry diets. Still, their use is limited due to the presence of non-starch polysaccharides (NSP) and phytates. The supply of leaves associated with exogenous enzymes can influence the weight, size, and morphology of the intestine, accessory glands, and reproductive system of laying hens. The aim was, therefore, to study the influence of MOL in diets supplemented with and without the enzymes xylanase and phytase, whether associated or not, and their effects on the size and weight of the organs of the gastrointestinal tract, accessory glands, and reproductive system, as well as on the morphological characteristics of the small intestine of laying hens intended for egg production during the peak laying period. A total of 288 laying hens of the Dekalb White strain aged 32 weeks were used, distributed in a completely randomized design in a 2 × 4 factorial arrangement (presence and absence of MOL x 4 forms of enzyme supplementation - with or without) for a total of eight treatments with six replicates of six birds per experimental unit. The treatments consisted of a control diet based on corn and soybean meal and a diet with 5% MOL supplementation followed by three forms of enzyme supplementation (xylanase, phytase, and a mix of the two enzymes). Xylanase, alone or in combination with phytase, played an essential role in reducing the relative size of the small intestine and caeca, as well as improving intestinal morphology by increasing villus height, crypt depth, villus height/crypt depth ratio, mucosal length, and villus width, thus characterizing improvements in the processes of digestion and absorption of nutrients. Phytase has not influenced the variables studied in this study. Dietary inclusion of Moringa oleifera leaf (MOL) and exogenous enzymes, particularly xylanase, significantly influenced organ weights and intestinal morphology in laying hens. Xylanase, especially when combined with MOL, enhanced villus height, crypt depth, V:C ratio, and mucosal length across all intestinal segments, while phytase had more variable effects depending on diet context. It can be concluded that the NSP present in MOL have various effects on the intestine, such as increasing the size of the intestine and attached glands and influencing intestinal morphometric characteristics. With the degradation of these nutrients, the action of xylanase re-establishes the birds’ intestinal health, which could lead to better performance from the layers.